Industry Marketing Mix Analysis Banana Chips In Konda Village One District Konda South Konawe Regency - Sisi Wulandari; Sarinah Sarinah; Muhammad Syukri (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2021)
This study aims to determine the effect of the marketing mix on product dimensions, price, place, and promotion on consumer satisfaction in the Simple Banana Chips Industry in Konda District, South Konawe Regency. Determination of the research location was done purposively. Data was collected using a questionnaire, interview, and documentation methods. The analysis used is Multiple Regression Analysis. Based on the results of research conducted on the analysis of the marketing mix of banana chips in the Simple Banana Chips Industry, it can be concluded that the results of the assessment and responses of consumer respondents to aspects of the marketing mix of product dimensions, price and place have a satisfied rating category where the average consumer chooses a scored answer four or agree. In contrast, the aspect of the marketing mix (promotion) has a poor rating category where the average consumer chooses an answer score of 3 or less satisfied and two or dissatisfied.